Application of Response Surface Method for Preparation, Optimization, and Characterization of Nicotinamide Loaded Solid Lipid Nanoparticles - Molood Alsadat Vakilinezhad; Shima Tanha; Hashem Montaseri; Rassoul Dinarvand; Amir Azadi; Hamid Akbari Javar (Tabriz University of Medical Sciences, 2018)
Purpose: Solid lipid nanoparticles (SLNs) have been proven to possess pharmaceutical advantages. They have the ability to deliver hydrophilic drugs through lipid membranes of the body. However, the loading of such drugs into SLNs is challenging. Hydrophilic nicotinamide, a histone deacetylase inhibitor, is used to establish SLNs with enhanced encapsulation efficiency by using statistical design. Methods: The possible effective parameters of these particles' characteristics were determined using pre-formulation studies and preliminary tests. Afterwards, the Response Surface Method (RSM) was utilized to optimize the preparation condition of SLNs. The effect of the amount of lipid, drug, surfactant, and the mixing apparatus were studied on particle size, zeta potential, and encapsulation efficiency of the obtained particles. The acquired particles were characterized in respect of their morphology, in vitro release profile, and cytotoxicity. Results: According to this study, all the dependant variables could be fitted into quadratic models. Particles of 107 nm with zeta potential of about -40.9 and encapsulation efficiency of about 36% were obtained under optimized preparation conditions; i.e. with stearic acid to phospholipon® 90G ratio of 7.5 and nicotinamide to sodium taurocholate ratio of 14.74 using probe sonication. The validation test confirmed the model's suitability. The release profile demonstrated the controlled release profile following the initial burst release. Neither the nicotinamide nor the SLNs showed toxicity under the evaluated concentrations. Conclusion: The acquired results suggested the suitability of the model for designing the delivery system with a highly encapsulated water soluble drug for controlling its delivery.